Pengaruh Kemiskinan Terhadap Kriminalitas di Kota Batam - Maria Natalia Lerabeni (Dialektika Publik, 2022)
Poverty as One of the Causes of Crime. This article aims to analyze more deeply the effect of poverty on criminal acts that occur in the city of Batam. This study uses a qualitative descriptive method. Data obtained from secondary data, namely using literature studies, collecting information from various journals, and the latest news to be used as data sources The results of the study show that the poverty line is increasing because the prices of necessities continue to soar, which has an impact on the difficulty of the community to survive. Criminal acts such as theft, mugging, robbery, and beheading are some crimes influenced by economic factors.